THE SACRAL NATURE OF STRAW MOSAIC BY OLEKSANDR SAJENKO (Review of the creative works of Ukrainian artist O.F. Sajenko) - Obushnyy, Mykola (Київський національний університет імені Тараса Шевченка, 2021)
The publication aims to draw the attention of Ukrainian scholars and researchers of Ukrainian cultural heritage to study the work of a unique domestic artist of monumental and decorative art, whose name is included in the list of prominent figures of world heritage of the twentieth century - Alexander Saenko. O. Saenko's artistic heritage includes more than 500 works of painting, graphics and monumental and decorative art: decorative panels, carpets, tapestries, etc. But O. Saenko possessed the technique of straw inlay most perfectly. He subtly felt the diversity of sacred energies that give "joy to people." It was in the colors of straw that O. Saenko saw such energy.O. Saenko's paintings are not only artistically perfect, but also the vast majority of them are filled with nationalpatriotic content. Among them, one of the most famous is the decorative painting "Kozak Mamai" (1928, 1936). The analysis of O. Saenko's paintings shows that they are deeply folk, and therefore perceived as modern in their content and style.

Публікація ставить за мету привернути увагу українознавців, дослідників української культурної спадщини до вивчення творчості унікального вітчизняного художника монументально-декоративного мистецтва, ім‟я якого внесено до списку видатних діячів світової спадщини ХХ століття – Олександра Ферапонтовича Саєнка. Мистецька спадщина О.Ф. Саєнка нараховує понад 500 творів малярства, графіки і монументально-декоративного мистецтва: декоративне панно, килими, гобелени і т.ін. Але найдосконаліше О.Ф. Саєнко володів технікою інкрустації соломкою. Він тонко відчував розмаїття сакральних енергій, які дарують «радість людям». Саме у кольорах соломи О.Ф. Саєнко бачив таку енергію. Картини О.Ф. Саєнка не тільки художньо досконалі, але, і переважна більшість із них наповнені національно-патріотичним змістом. Серед них одна із найвідоміших – декоративна картина «Козак Мамай» (1928, 1936 рр.). Аналіз картин О.Ф. Саєнка показує, що вони є глибоко народними, а тому сприймаються як сучасні своєю змістовою наповненістю та стилістично.
САКРАЛЬНІСТЬ МОЗАЇКИ СОЛОМОЮ ХУДОЖНИКА ОЛЕКСАНДРА САЄНКА (Рецензія на творчість українського художника О.Ф. Саєнка)
Keywords: sacredness; straw; artist; monumental and decorative art; inlay; mosaic; genetic memory; сакральність; солома; художник; монументально-декоративне мистецтво; інкрустація; мозаїка; генетична пам'ять